(untitled) (Altre Modernità, 2019)
This paper analyzes the use of multiple linguistic codes in audiovisual products and in translation, taking as a case study Paolo Sorrentino’s TV series The Young Pope (2016). In spite of the various studies that claim that multilingual audiovisual products tend to represent a more realistic depiction of modern society from a sociolinguistic perspective, the results of the analysis seem to demonstrate that this is not always the case. Indeed, the use of languages in the TV series is realistic only to a certain extent, as English tends to be used even when it would be reasonable to expect people to speak Italian. Likewise, linguistic realism is not a priority also in the Italian version, where all languages have been dubbed into standard Italian, regardless of the origins of the speakers.